KaiC family proteins integratively control temperature‐dependent UV resistance in Methylobacterium extorquens AM1. Issue 6 (17th September 2018) - Iguchi, Hiroyuki; Yoshida, Yusuke; Fujisawa, Kento; Taga, Hiroki; Yurimoto, Hiroya; Oyama, Tokitaka; Sakai, Yasuyoshi
Summary: KaiC protein is the pivotal component of the circadian clock in cyanobacteria. While KaiC family proteins are well‐conserved throughout divergent phylogenetic lineages, studies of the physiological roles of KaiC proteins from other microorganisms have been limited. We examined the role of the KaiC proteins, KaiC1 and KaiC2, in the methanol‐utilizing bacterium Methylobacterium extorquens AM1. Wild‐type M. extorquens AM1 cells exhibited temperature‐dependent UV resistance (TDR) under permissive growth temperatures (24 °C –32 °C). Both the phosphorylation of KaiC2 and the intracellular levels of KaiC1 were temperature‐dependent, and the TDR phenotype was positively regulated by KaiC1 and negatively regulated by KaiC2. Taken together with biochemical and functional analogies to the KaiC protein of cyanobacteria, our present results suggest that KaiC family proteins function to integrate environmental cues, that is, temperature and UV light, and output appropriate cellular responses to allow cells to adapt to changing environmental conditions.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd